2006
DOI: 10.1111/j.1600-6143.2005.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Versus Azathioprine in Maintenance Lung Transplant Recipients: An International, Randomized, Double-Blind Clinical Trial

Abstract: Everolimus is a proliferation signal inhibitor with immunosuppressive activity that may reduce the rate of progression of chronic rejection, bronchiolitis obliterans syndrome (BOS), after lung transplantation. In a randomized, double-blind clinical trial, 213 BOS-free maintenance patients received everolimus (3 mg/day) or azathioprine (AZA, 1-3 mg/kg/day) in combination with cyclosporine and corticosteroids. The prospectively defined primary endpoint was the incidence of efficacy failure (decline in FEV 1 >15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 34 publications
3
96
0
2
Order By: Relevance
“…Studies of bronchiolitis obliterans syndrome (BOS) in lung transplantation provide a common example of this analytic approach, where the main outcome is chronic rejection-free survival (50, 51) ( Figure 2). As another example, a recent randomized controlled trial of maintenance immunosuppression in lung transplantation evaluated a primary composite endpoint of lung function worsening (FEV 1 change .15%), graft loss, or death (52). As with all analytic approaches, the pros must be weighed against the cons for the use of combined endpoints.…”
Section: Outcomes Assessment In Lung Transplantation: Integrating Quamentioning
confidence: 99%
“…Studies of bronchiolitis obliterans syndrome (BOS) in lung transplantation provide a common example of this analytic approach, where the main outcome is chronic rejection-free survival (50, 51) ( Figure 2). As another example, a recent randomized controlled trial of maintenance immunosuppression in lung transplantation evaluated a primary composite endpoint of lung function worsening (FEV 1 change .15%), graft loss, or death (52). As with all analytic approaches, the pros must be weighed against the cons for the use of combined endpoints.…”
Section: Outcomes Assessment In Lung Transplantation: Integrating Quamentioning
confidence: 99%
“…109 A randomised multicenter study showed that BOS-free lung transplant recipients had significantly smaller decline in FEV1 and experienced fewer acute rejections when treated with everolimus compared with azathoprine. 110 Everolimus has been shown to give a significant survival benefit compared to those treated with MMF. 111 Cyclosporine and tacrolimus inhibit calcineurin, thereby decreasing IL-2 production and reducing T-cell activation/proliferation.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Table 36 summarizes the two studies in which everolimus administration was studied in lung transplant patients. 316,516 3.6.1.1 Toxicity-Leukopenia, thrombocytopenia, and anemia occur commonly with everolimus. Other common adverse effects include hypercholesterolemia, hyperlipidemia, hypertriglyceridemia, and hypertension.…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…325 A summary of 11 studies supporting recommendations for the monitoring of AZA in patients with lung disease and organ transplant recipients is provided in Table 28 . [310][311][312]314,316,317,320,[322][323][324]326 3.5.1.1 Toxicity-Common adverse reactions associated with azathioprine include leukopenia, 327 pancreatitis, 328 and hepatitis. 329 Other effects of bone marrow toxicity include thrombocytopenia, anemia, megaloblastic anemia, aplastic anemia, eosinophilia, myelodysplastic syndrome, and fatal acute myeloid leukemia.…”
Section: Information For Patientsmentioning
confidence: 99%
See 1 more Smart Citation